Edukasi Pemilahan dan Pengelolaan Jenis Sampah di SDN 007 Pangkalan Baru Kecamatan Siak Hulu Kabupaten Kampar - Arief Yandra Putra; Putri Ade Rahma Yulis (Community Education Engagement Journal, 2019)
Environmental problems are global issues caused by low public awareness of the importance of environmental management. One factor is the environmental pollution generated by waste. The problem of waste is closely related to the lifestyle and culture of the community. If waste management does not get the attention of various parties, it will make environmental conditions worse and human health conditions also go down. Therefore, awareness of the importance of waste management needs to be instilled since childhood. This activity was carried out at SDN 007 Pangkalan Baru, Siak Hulu District, Kampar Regency. Based on the activities that have been carried out, most students do not yet understand how to classify and process waste to be economic value so the education should be given to the students. This activity can be said successful because of the high enthusiasm and participation of students in answering the questions that given based on the material that has been delivered.